A comparative study on functional outcome of unstable intertrochanteric fractures in elderly treated with bipolar hemiarthroplasty and dynamic hip screw fixation: a short term perspective analysis - Anand, M. R.; Ramachandren, N. S. (International Journal of Research in Orthopaedics, 2020)
Background: Trochanteric hip fractures in elderly patients have benefited from advances in internal fixation. Early failure of internal fixation occurs however in a number of cases. The failure after internal fixation had been due to initial fracture pattern, communication, sub-optimal fracture fixation and poor bone quality. The aim of this prospective comparative study is to analyze the short term follow up results of unstable Intertrochanteric fractures in elderly treated with bipolar hemiarthroplasty and dynamic hip screw (DHS) fixation. Methods: This is a study conducted in the Department of Orthopaedics, Government Tiruvarur Medical College, Tiruvarur. 42 elderly osteoporotic patients with unstable intertrochanteric fractures who were divided into two groups with group A-bipolar prosthesis (21 cases) and group B-DHS (21 cases). Results: 42 elderly osteoporotic patients with unstable intertrochanteric fractures who were divided into two groups with group A-bipolar prosthesis (21 cases) and group B-DHS (21 cases). Patients were evaluated clinically using the Harris hip score during their follow up period. In both groups, the most common Singh’s index was grade III, 61.90%in both group A and group B. Conclusions: From our results, we are of the opinion that bipolar hemiarthroplasty may be an efficient option in elderly osteoporotic intertrochanteric fractures. It reduces the potential complications of prolonged immobilization such as pressure sores, pulmonary complications by early mobilization.